Robust Stability Analysis of a Class of Smith Predictor-based Congestion Control Algorithms for Computer Networks - Luca De Cicco; Saverio Mascolo; Silviu-Iulian Niculescu (8th IFAC Workshop on Time-Delay Systems, 2009)
Congestion control is a fundamental building block in packet switching networks such as the Internet due to the sharing of communication resources. It has been shown that the plant dynamics is essentially made of an integrator plus time delay and that a proportional controller plus a Smith predictor is a simple and effective controller. It has been also shown that the today running TCP congestion control can be modelled using a Smith predictor plus a proportional controller. Due to the importance of this control structure in the field of data network congestion control, we analyze the robust stability of the closed loop system in the face of delay uncertainties that in data networks are present due to queuing. In particular, by applying a geometric approach, we derive a bound on the proportional controller gain which is necessary and sufficient to guarantee stability given a bound on the delay uncertainty.
Keywords: Time-delay systems; Robust stability; Congestion control; Smith predictor